Accounting and Finance Literacy and Entrepreneurship: an Exploratory Study - Trombetta, Marco (Elsevier, 2023)
The aim of this study is to investigate whether the level of financial literacy differs significantly among entrepreneurs in three European countries: Italy, Spain, and the UK. Moreover, I analyze whether financial literacy fosters or hinders entrepreneurial resilience and success. I find that the level of basic financial literacy is significantly lower among entrepreneurs in the UK. I provide an explanation based on job opportunities arguing that basic financial literacy increases the chances of survival of a business, whereas advanced financial literacy decreases it. I propose a taxonomy linking levels of financial literacy with different approaches to financial management. I conclude that a “conservative” approach to financial management (cash based, debt-averse and diversified) is more likely to guarantee survival even if it is not necessarily the best way to maximize firm value.
Keywords: 53 Ciencias Económicas; ODS 3 - Salud y bienestar; ODS 1 - Fin de la pobreza; ODS 10 - Reducción de las desigualdades